In vitro investigation of potential anti-diabetic activity of the corm extract of Hypoxis argentea Harv. Ex Baker (2018)
The corms of Hypoxis argentea are widely used as a traditional remedy for diabetes mellitus in South Africa. In this study, we investigated the effects of non-toxic concentrations (12.5–100 μg mL–1) of the aqueous extract of H. argentea (HAA) corms on glucose uptake, pancreatic beta cell proliferation, and adipocyte differentiation. HAA stimulated glucose uptake in HepG2 cells up to 19.6 % and 17.0 % in L6 myotubes. Live-cell imaging microscopy revealed significant increases (p < 0.001) in total INS-1 cell numbers exposed to HAA, although no effect was observed on adipogenesis in 3T3-L1 pre-adipocytes. HAA produced weak to moderate inhibition of porcine pancreatic α-amylase, α-glucosidase, porcine pancreatic lipase, dipeptidyl peptidase IV (DPP IV) activities, as well as protein glycation. Our results suggest that the acclaimed anti-diabetic effects of H. argentea could be mediated by its promotion of glucose utilization and preservation of pancreatic beta cell populations while preventing fat accumulation in adipocytes.